2014
DOI: 10.1111/ctr.12422
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal muscle group area and surgical outcomes in liver transplantation

Abstract: INTRODUCTION Better measures of liver transplant risk stratification are needed. Our previous work noted a strong relationship between psoas muscle area and survival following liver transplantation. The dorsal muscle group is easier to measure but it is unclear if they are also correlated with surgical outcomes. METHODS Our study population included liver transplant recipients with a preoperative CT scan. Cross-sectional areas of the dorsal muscle group at the T12 vertebral level were measured. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 14 publications
2
82
1
1
Order By: Relevance
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
“…The methods of muscle measurement and sarcopenia definitions that were used are summarized in Table 2. Nine studies reported the cross-sectional muscle area with corresponding skeletal muscle index (12)(13)(14)17,(22)(23)(24)(25)30), whereas the psoas area was reported in eight studies (15,16,18,19,21,(26)(27)(28) and the dorsal muscle group area was reported in one study (20). One study calculated the morphometric age (calculated with total psoas area, psoas density, and abdominal aortic calcifications) (29).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations